Comparação de tecnologias de gaseificação de biomassa para substituição do gás natural em plantas de pelotização de minério de ferro - Mariana Machado de Oliveira Carvalho (2014)
The iron ore pelletizing process consumes high amounts of energy, including non-renewable sources, such as natural gas. Due to fossil fuel scarcity and increasing concerns regarding sustainability and global warming, at least partial substitution by renewable energy seems inevitable. Gasification projects are being successfully developed in Northern Europe, and largescale circulating fluidized bed biomass gasifiers have been commissioned in e.g. Finland. As Brazil has abundant biomass resources, biomass gasification is a promising technology in the near future. Biomass can be converted into product gas through gasification. This work compares different technologies, such as air, oxygen and steam gasification, focusing on the use of the product gas in the indurating machine. The use of bio-synthetic natural gas is also evaluated. The main parameters utilized to assess the suitability of product gas were adiabatic flame temperature and volumetric flow rate. It was found that low energy content product gas could be utilized in the traveling grate, but it would require burners to be changed. On the other hand, bio-SGN could be utilized without any adaptions. Economical assessment showed that all gasification plants are feasible for sizes greater than 60 MW. Bio-SNG production is still more expensive than natural gas in any case.